Sufficiency and the Shifting Dynamics of Efficiency: A Political Economy and Jurisprudence Review - Efendi, Muhammad Syarahil Mutianwar; Maulana, Reza Ilham (Mimbar Hukum, 2025)
Abstract Sufficiency is a concept that challenges efficiency, a rational consequence that hitherto grows within the logic of capitalism. Without efficiency, the structure of capitalism collapses, as it has become the ontological prerequisite sustaining the structure of production, distribution, and accumulation of capital; Contrarily, efficiency leads to the collapse of the Earth’s systems, as it inherently overlooks ecological boundaries and fails to recognize the limits of nature as a fundamental principle in economic activity. This article examines, from a normative perspective, the transformative potential of sufficiency through an epistemic assertion within political economy and jurisprudence. It explores how this concept can redefine the relationship between economics, ethics, and ecology, advocating for a more balanced approach to socio-ecological justice that benefits both humans and nature. Intisari Sufisiensi adalah sebuah konsep yang menantang prinsip efisiensi, sebuah konsekuensi rasional yang sampai saat ini tumbuh dalam logika kapitalisme. Tanpa efisiensi, struktur kapitalisme akan runtuh, karena telah menjadi prasyarat ontologis yang menopang struktur produksi, distribusi, dan akumulasi kapital; sebaliknya, efisiensi menyebabkan runtuhnya sistem bumi karena secara inheren mengabaikan batas-batas ekologis dan gagal mengenali batas-batas alam sebagai prinsip fundamental dalam aktivitas ekonomi. Artikel ini mengkaji, dari perspektif normatif, potensi transformatif dari konsep sufisiensi melalui argumentasi epistemik dalam ekonomi politik dan filsafat hukum. Artikel ini mengeksplorasi bagaimana konsep sufisiensi dapat mendefinisikan kembali hubungan antara ekonomi, etika, dan ekologi, mengadvokasi pendekatan yang lebih setimbang terhadap keadilan sosio-ekologis bagi manusia dan alam.